Penggunaan Teknologi Blockchain Pada Pembiayaan Akad Qardh Terhadap Kualitas Laporan Keuangan Pada Bank BJBS KC Pelajar Pejuang Kota Bandung - Aulia Falent Az Zahra; Iwan Setiawan (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This paper aims to examine the Use of Blockchain Technology in Qardh Contract Financing on Financial Reports at Bank BJBS KC Pelajar Pejuang, Bandung City. The descriptive method and exploratory analysis are the research methods employed, along with text studies in the form of linked data and studies of diverse literatures that are also based on existing data or investigations meant to solve current problems. Library research is the method used in this study to gather data. In order to provide corroborating references on scientific theories that may be relevant to the study issue during the report-writing process, library research is carried out by examining books and other forms of scientific writing media. The study's findings indicate that Bank BJBS KC Pelajar Pejuang, Bandung City's financial reports are significantly improved by the application of blockchain technology in Qardh (pawn) contract financing.